SEMANTIC STUDY OF UNITS EXPRESSING GRATITUDE IN THE UZBEK LANGUAGE (World Bulletin of Social Sciences, 2024)
In this scientific work, the lexical units expressing gratitude in the Uzbek language and their semantic features are studied. In the culture and language of Uzbekistan, gratitude has a great place, and it is important not only in personal relationships, but also in social relations in society. In this study, through the semantic analysis of words and phrases expressing gratitude, their place in linguistics, grammatical and stylistic features, as well as how they fit into the social and cultural context of the language are studied. The study mainly focuses on the following lexical units: words and phrases such as "thank you", "thank you", "thank you very much", "thank you for your help". Their semantic load, layers of meaning, their use in many situations and the differences between different social layers are analyzed. Also, the role of expressions of gratitude in speech, their role in strengthening relationships between people, and elements expressing respect in language (holidays, birthdays, titles, respect for age) are analyzed.
Keywords: semantics; gratitude; unity; exploration